Knowledge management as a management function - A. B. Zudin; L. D. Gurtskoy; P. I. Ananchenkova (Здоровье мегаполиса)
Introduction. Due to rapid expansion of the global knowledge-based economy many organizations, including medical ones, have to find and implement the most appropriate knowledge capital solutions that will enable them to achieve sustainable competitive advantages.Background. The paper is aimed to provide theoretical overview of the knowledge management concept in the management system, its functions, effects and advantages of implementation in medical organizations.Materials and methods. Analysis and synthesis of scientific publications were used to define the conceptual idea of knowledge management, its functions, principles, advantages, implementation and application.Results. The study showed that knowledge management (KM) as a concept and a management function remains understudied in modern scientific literature. In terms of strategic management and sustainable development of medical organizations, scientific works studying KM are poorly presented, which does not allow to fully assess the prospects and possibilities of knowledge management in medicine and healthcare.